The Influences of People and Local Culture on Purchase Decision Moderated By Social Media Marketing on Traditional Product of MSMEs in East Kotawaringin Regency of Central Kalimantan - Asi, Yuli Sintha; Assagaf, Aminullah; Indrasari, Meithiana; Yunus, Eddy; Sukesi; Riyadi, Slamet; Suyanto (Dinasti Publisher, 2024)
The aim of this paper to analyze the influence of people and local culture on purchase decision which is moderated by social media marketing. The research is the descriptive quantitative The research findings are as follows (1). People influences purchase decision with sig. 0.049. (2). Local culture influences purchase decision with sig. 0.001. (3) People and Local culture simultaneously influence purchase decision. F table is 18.770 > 2.87 with sig. 0.000. People and local culture also show positive and significant influence on purchase decision.